The New (Old) Case for the Ethics of Business - Wolcott, Gregory (Journal of business ethics, 2015)
In this paper, I argue for the ethics of business based on the way that business activity may embody a vocation to partake in “the Good.” Following a Platonist framework for ethics and recent work on vocations by Robert M. Adams, I argue that understanding the ethics of vocations allows us to avoid the charges that business persons have to do something more for others—often couched in terms of social responsibility, sustainability, or consideration of stakeholders—in order to legitimize their careers ethically. Rather, I claim, the ethics of a business vocation, as in any vocation, rests first and foremost in the way that a person pursues projects that answer an invitation to partake in the good things of this world. Thus, the promotion of the well-being of others, while ethically admirable and constitutive of some vocations, is not fundamental for understanding the ethics of vocations themselves, even in business. There are important implications for the ethics of markets, and I also consider a recent challenge to my approach that claims that true business vocations demand a more direct promotion of the well-being of others.